“Duduk Dekat di Bawah Guru” dan Transformasinya: Kajian atas Kitab Upanisad dalam Ajaran Hindu - Segara, I Nyoman Yoga (Jurnal Lektur Keagamaan, 2016)
This article is the result of the study of literature on the scripture of the Upanisad, one of the most important in the Hindu scriptures. Upanisad becomes an integral part of the Vedas, even being sakha to describe the contents of Catur Veda Samhita. This position reinforces the belief of Hindus that the Upanisad is Vedanta, which on further development inspires other scriptures, especially Darsana, and also Bhagawadgita. The contents of the principal Upanisads primarily discuss the concept of God (Brahman), the human and the atman, the beginning and end of the universe, death, karma and reincarnation, and also dreams. But in general, the main content of Upanisad reflects about the sraddha, and Hindu philosophy. Actually, the content of the Upanisad is very heavy, but this scripture is relatively easy to read because it is served with a dialogue style and the narrative is rich in analogies. In addition Upanisad literally translated as â€œto sit down near the teacherâ€, as well as imagination on indepth dialogue between teacher and student, although the main content of the Upanisad has exceeded its basic meaning. Keywords: Upanisad, Catur Veda Samhita, Vedanta, Sraddha, Hindu Philosophy, Scriptures Artikel ini adalah hasil kajian kepustakaan terhadap kitab Upanisad, salah satu kitab suci terpenting dalam Hindu. Upanisad menjadi bagian tak terpisahkan dari Weda, bahkan menjadi sakha untuk menjabarkan isi Catur Weda Samhita. Posisi ini memperkuat keyakinan umat Hindu bahwa Upanisad adalah Wedanta, yang pada perkembangan selanjutnya mengin-spirasi kitab-kitab suci lainnya, terutama Darsana, dan juga Bhagawadgita. Adapun isi pokok Upanisad membahas banyak konsep tentang Tuhan (Brahman), manusia dan atman, awal dan akhir semesta, kematian, karma dan reinkarnasi, juga mimpi. Namun secara umum, isi pokok Upanisad merefleksikan tentang sraddha, dan filsafat Hindu. Sebenarnya, isi Upanisad sangatlah berat, namun kitab ini relatif mudah dibaca karena disajikan dengan gaya dialog dan narasinya kaya analogi. Selain secara harafiah Upanisad diartikan sebagai â€œduduk dekat di bawah guruâ€, juga karena imajinasi atas dialog mendalam antara guru dan murid, meskipun isi pokok Upanisad telah melampui pengertian dasarnya ini. Kata Kunci: Upanisad, Catur Weda Samhita, Wedanta, Sraddha, Filsafat Hindu, Kitab Suci.